Tracing the Shift in Quality Management Paradigms: A Systematic Review of Taylor, Shewhart, and Deming in the Context of Islamic Education - Hesty Widiastuty; Fauzi Fauzi; Dakir Dakir (Tarbawi: Jurnal Keilmuan Manajemen Pendidikan, 2025)
This study aims to systematically analyze the evolution of quality management paradigms and investigate their integration potential within Islamic educational institutions. Employing a Systematic Literature Review (SLR) methodology following PRISMA guidelines, the researchers examined 18 high-quality articles from Scopus-indexed journals. The findings reveal that traditional quality theories remain relevant but require thoughtful adaptation in the digital era. Three main themes emerged: the evolution and potential tensions between quality management theories, the transformative and empowering role of statistical process control in educational assessment, and the impact of Industry 4.0 technologies on quality assurance in Islamic education contexts. The researchers propose an "Islamic Education Quality 4.0" framework that integrates technological advancements with Islamic educational principles, balancing data-driven decision-making with ethical considerations rooted in Maqasid Syariah. This research contributes to the theoretical understanding and practical implementation of integrated quality management approaches in Islamic educational institutions, emphasizing the need for contextually appropriate quality models that enhance operational excellence while preserving core spiritual values.